2013
DOI: 10.3109/09513590.2013.801449
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin receptor autoantibodies and early miscarriages in patients with Hashimoto thyroiditis: a case–control study

Abstract: We have previously hypothesized that early miscarriage in women with Hashimoto thyroiditis might be the result of a cross-reactivity process, in which blocking autoantibodies against thyrotropin receptor (TSHr-Ab) antagonize hCG action on its receptor on the corpus luteum. To test this hypothesis from the clinical perspective, we investigated the presence of TSHr-Ab in Hashimoto thyroiditis patients with apparently unexplained, first-trimester recurrent miscarriages compared to that in Hashimoto thyroiditis pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although the TSH-like actions of hCG require further research, a 2009 study suggested a link between thyroid autoimmunity and miscarriage 71 . However, conflicting data raise concerns about this hypothesis 72 . Finally, gestational hyperthyroidism has been linked to the expression of TSHR gene variants with hCG hypersensitivity 73 .…”
Section: Recent Advancesmentioning
confidence: 99%
“…Although the TSH-like actions of hCG require further research, a 2009 study suggested a link between thyroid autoimmunity and miscarriage 71 . However, conflicting data raise concerns about this hypothesis 72 . Finally, gestational hyperthyroidism has been linked to the expression of TSHR gene variants with hCG hypersensitivity 73 .…”
Section: Recent Advancesmentioning
confidence: 99%
“…Nevertheless, approximately 79.3% of HT patients display a euthyroid state at diagnosis and may retain normal thyroid function for many years [8, 9]. In recent years, the association between euthyroid HT and pregnancy loss has drawn attention [10, 11]. Data from the literature suggest that the leading single cause of pregnancy failure is embryo implantation error, which can occur at a rate of up to 78% in humans [12].…”
Section: Introductionmentioning
confidence: 99%